Molecular Heterogeneity of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency in the Portuguese Population - Manco, Licínio (2022)
Introduction: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme defect in the world, affecting more than 500 million people. In Portugal, the average frequency of G6PD deficiency in males was estimated at about 0.5% and since the year 2000 several G6PD-deficient alleles have been identified. The main goal of this study was to improve the knowledge on the molecular heterogeneity of G6PD deficiency in the Portuguese population.Material and Methods: A retrospective analysis of the mutational profile of 138 unrelated Portuguese individuals (101 males; 37 females), with no known sub-Saharan ancestry, who had been diagnosed with G6PD deficiency between 1994 and 2020 at the Molecular Hematology Unit of Centro Hospitalar e Universitário de Coimbra. The molecular study was done by direct Sanger sequencing or PCR-RFLP analysis.Results: Twenty-one different pathogenic mutations were found. Among them, 20 were missense, causing the amino acid change, and one was an in-frame deletion in exon 10. The three most frequent mutations belong to the G6PD c.376A>G African background haplotype, namely the G6PD variants: A- (c.202G>A; p.68Val>Met) (58.6%), Betica (c.968T>C; p.323Leu>Pro) (12.1%) and Santamaria (c.542A>T; p.181Asp>Val) (4.3%).Conclusion: There is a wide molecular heterogeneity of G6PD deficiency in the Portuguese population.